Exploring the Antibacterial Activity of Banana Peel Waste From Agung Semeru Variety in Lumajang againts Gram Positive and Gram-Negative - Rikhmasari, Dwi Nur; Ratih Purwandari, Anggraini (BIO-CONS : Jurnal Biologi dan Konservasi, 2025)
Banana peels, a by-product of banana consumption, remain underutilized despite their promising bioactive potential. This study aims to assess the antibacterial properties of the peel extract from the Agung banana variety (Musa paradisiaca var. sapientum L.) against two pathogenic bacterial strains: Pseudomonas aeruginosa and Staphylococcus aureus. The extract was prepared through a maceration method, and antibacterial activity was tested using the disk diffusion technique. A Completely Randomized Design (CRD) was employed, involving five concentration levels (0%, 25%, 50%, 75%, and 100%) with four replicates each. Data were analyzed using ANOVA, followed by Duncan’s Multiple Range Test (DMRT) to determine significant differences between treatments. The results demonstrated that the Agung banana peel extract significantly inhibited the growth of both test bacteria. The 100% concentration yielded the largest inhibition zones, with mean diameters of 17.55 ± 3.39 mm for P. aeruginosa and 19.25 ± 0.91 mm for S. aureus. According to the classification of antibacterial strength, these results are considered strong. These findings suggest that the Agung banana peel has considerable potential as a natural and eco-friendly antibacterial agent.